The Obstacles of Indonesia-Iceland Cooperation In the Development of Geothermal Energy in Indonesia (2007-2014) - Bestari, Althea S; Rudiany, Novita Putri (Journal of International Relations on Energy Affairs, 2020)
This paper discusses the obstacles in Icelandic-Indonesian cooperation related to geothermal development in Indonesia in 2007 - 2014. In the cooperation process that prioritizes geothermal energy use in Indonesia, the interaction between Iceland and Indonesia has not shown significant implementation results, mainly technical geothermal energy exploration. This cooperation has been going on for seven years. The concept of Barriers to International Cooperation developed by Lauri Siitonen, which is a derivative of the idea from Theories of International Cooperation, is used to analyze existing obstacles. This concept explains why cooperation and obstacles can occur due to the interactions of the actors involved. In this case, each country's national interests, which become the foundation for interactions in the international system, can create political policies that often ignore bilateral cooperation objectives. This research is based on primary data and secondary data with descriptive-analytical methods. This paper's conclusion shows that political and policy factors and technical factors are significant in hindering this cooperation.